What Lessons can the Luckin Coffee Scandal Offer to Australia–China Cross-Border Listed Companies’ Supervision? Problems and Reform Suggestions in China - Guo, Qi (Columbia Journal of Asian Law, 2022)
The continuous disclosure compliance of Chinese cross-border companies listed in Australia has long been a concern, as Chinese companies are either frequently delisted or rejected by the Australian Securities Exchange. The particularity of cross-border listings generates information asymmetry between securities regulators based out of the host jurisdiction and the home jurisdiction. This then impacts the effectiveness of the host jurisdiction’s supervision of the cross-border listed companies and each company’s continuous disclosure compliance. The purpose of this article is to clarify the issues surrounding cross-border supervision by the securities regulators in China to shed light on current dilemmas and suggest possible reform proposals. Considering the similarities of the securities markets in the US and Australia, as a case study example, this article looks at Luckin Coffee, a US-listed Chinese company, which created a scandal in 2020 when it was accused of continuous disclosure fraud. The case points out relevant lessons for Australia–China securities cross-border supervision.